Clinical profile of patients presenting with dengue fever visiting the emergency department of Gandaki Medical College: A cross-sectional study - Gautam, Bijaya; Pokhrel, Shanti; Banstola, Laxman; Dahal, Meghnath (Journal of Gandaki Medical College-Nepal, 2026)
Introduction: Dengue fever is a self-limiting acute illness that occurs with dengue virus, whose vector is mosquitoes Aedes aegypti and Aedes albopictus. Dengue spread from person to person via infected mosquito, the primary vector being Aedes aegypti. Clinical features ranges from febrile phase to clinical phase and finally recovery phase. Warning signs of dengue fever are pain abdomen, persistent vomiting, fluid accumulation states like ascites or pleural effusion, bleeding from mucosa, lethargy, hepatomegaly greater than 2 cm, increase in hematocrit, including leukopenia and thrombocytopenia. Hence, this study aimed to evaluate clinical profile of dengue patients.Methods: This was a cross-sectional study where dengue fever was diagnosed based on serology (Ns1). The clinical parameters and laboratory findings were recorded after obtaining verbal and written consent.Results: Out of 170 dengue patients, mean age were 38.21(±16.5) years with a female:male ratio of 1.1:1. Majority had fever 164(96.5%) followed by headache 91(53.5%), retro-orbital pain 80(47.1%) and myalgia 112(65.9%). Most common feature of warning sign was abdominal pain 33(60%). Our study showed 91(53.5%) dengue patient had thrombocytopenia. This study showed the statistically significance between warning signs and thrombocytopenia(p